2014
DOI: 10.1111/jop.12265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methotrexate upon antigen‐induced arthritis of the rabbit temporomandibular joint

Abstract: Systemic administration of MTX seems to have a positive effect upon the inflammatory process in the rabbit TMJ but fails to eliminate the sign of arthritis completely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…After antigen injection has been recognized as a successful and reliable method for inducing arthritis of the knee joints in rabbits, the antigen-induced arthritis (AIA) in TMJ of the rabbit has been chosen by numerous researchers. 31 Arthritis was induced with an intra-articular administration of ovalbumin in 10-week-old male New Zealand white rabbits. Antigen-treated joints demonstrated severe arthritis symptoms, involving mononuclear cell infiltration, synovial lining, villous hyperplasia, and pannus formation, which maintain from 5 to 55 days post-operation.…”
Section: Animal Models Of Tmdmentioning
confidence: 99%
“…After antigen injection has been recognized as a successful and reliable method for inducing arthritis of the knee joints in rabbits, the antigen-induced arthritis (AIA) in TMJ of the rabbit has been chosen by numerous researchers. 31 Arthritis was induced with an intra-articular administration of ovalbumin in 10-week-old male New Zealand white rabbits. Antigen-treated joints demonstrated severe arthritis symptoms, involving mononuclear cell infiltration, synovial lining, villous hyperplasia, and pannus formation, which maintain from 5 to 55 days post-operation.…”
Section: Animal Models Of Tmdmentioning
confidence: 99%
“…Methotrexate is the only medication with significant evidence in the treatment of TMJ arthritis [57] and is usually first line in practice for JIA with TMJ involvement. Weekly intramuscular injection of methotrexate has been shown to decrease cartilage degeneration in rabbits with antigen-induced arthritis but failed to eliminate arthritis completely [64]. Furthermore, in a cross-sectional study, Ince et al demonstrated that methotrexate therapy may minimize TMJ destruction in polyarticular JIA.…”
Section: Conventional Dmardsmentioning
confidence: 99%
“…Araştırmada, MTX'in sistemik olarak uygulanmasının, tavşan TME'nin enflamatuar süreci üzerinde olumlu etkiye sahip olduğu ancak artrit belirtilerinin tamamen ortadan kaldırılamadığı bildirilmiştir. 37 Araştırmamızda bu çalışmaların 7tepeklinik sonuçlarından farklı olarak MTX kullanan ve kullanmayan olgular arasında ağrı, ses, kısıtlı hareket, retrognati ve anterior open-bite görülme oranları açısından istatistiksel olarak anlamlı bir farklılık bulunmamıştır. TME tutulumunun değerlendirilmesinde araştırmamızda, TME'nin klinik muayene bulguları değerlendirilmiş, radyografik olarak bir değerlendirme yapılmamıştır.…”
Section: Gereç Ve Yöntemunclassified